Poverty alleviation strategies and new economic model in Malaysia - Mohamed, Mohd Zin; John Antony, Xavier (Academic Research Publishers, 2015)
Poverty eradication remains high on the national agenda. Malaysia’s seriousness about poverty eradication - one of the millennium development goals - has enabled it to achieve a drastic reduction of the poverty rate from 60% in the 1970s to 3.8% in the 20009. Hard core poverty has been virtually eliminated, declining to 0.7% in 2009. Although the incidence of poverty is low, pockets of poverty exist with high incidence among specific ethnic groups and localities.The New Economic Model (NEM) takes the fight against poverty to even further heights. Unveiled in 2010, the NEM is the roadmap to double Malaysia’s current per capita income of USD 7,000 to USD 15,000-17,000 by 2010 and, thereby, qualify as a high-income country in line with its Vision 2020. This ambition causes the NEM to focus on the lower 40% income households who have experienced a relatively flat income growth rate compared to those in the top 20% and middle 40% households who have enjoyed steep income growth rates over the last three decades. Combining descriptive and analytical methods involving interviews with selected high-level officials directly involved in poverty eradication and secondary data, the paper evaluates Malaysia’s efforts at poverty eradication over the last 50 years. It highlights the approach taken by the NEM in combating poverty. Much of Malaysia’s success has been the result of its macro- and micro-management of poverty eradication. At the macro level, policies and plans spell out the broad strategies to conquer poverty.The determination of poverty eradication as one of the six national key result areas brings poverty eradication under micro scrutiny. Specific policy initiatives and programmes are being implemented to wipe out pockets of poverty.The practical value of this paper is that it offers policy-makers a digest of workable strategies critical success factors in poverty eradication.